Preparation and Immobilization of Oxalate Oxidase Nanoparticles onto Au Electrode for Amperometric Determination of Oxalate in Urine and Plasma - Pundir, Chandra S; Rachita,; Pundir, Shikha (International Journal of Applied Sciences and Biotechnology, 2026)
The determination of oxalate in the biological fluid is of great importance in the diagnosis and medical management of urinary stone disease and various intestinal diseases. We describe herein preparation of oxalate oxidase (OxOx) nanoparticles (NPs) and their electrodeposition / imobilization onto Au electrode for improved amperometric determination oxalate in serum and urine. An oxalate biosensor was fabricated by connecting OxOxNPs,AgCl as standard electrode and Pt wire as auxillary electrode through potentiostat/Galvanostat. OxOxNPs were characterized by transmission electron microscopy (TEM). The enzyme electrode was characterized by scanning electron microscopy (SEM) and   cyclic voltammetry (CV). The biosensor showed optimum response within 3s at pH5.5 and 350C, when operated at 0.345V. The biosensor exhibited excellent sensitivity with a detection limit (LOD) as low as   1 µM, fast response time and wider linear range (from1 to 400 µM). Michaelis Menten constant (Km) for OxOxNPs was 15.19 µM and Imax 0.001 mA.  Analytic recoveries of exogenously added oxalate in urine (20 µM, 40 µM) were 97.5% and 99.1% respectively. Within and between batch coefficients of variation for urinary oxalate determination were